The impact of the COVID-19 pandemic on the lifestyle of students of the State University of Applied Sciences in Nowy Sącz - Marek Zborowski; Anna Mikulec; Urszula Cisoń-Apanasewicz; Stanisław Kowalski (Kazimierz Wielki University, 2023)
Introduction A properly balanced diet and physical activity guarantee health and good psychophysical condition. The timing of the pandemic is associated with numerous limitations affecting food preferences and physical activity. Aim The study aimed was to determine the impact of pandemic isolation on student activity and dietary habits during COVID-19 isolation. Material and methods The study group consisted of students (n = 526) of the State University of Applied Sciences in Nowy Sacz. The research was an online survey (Google Forms). The questions included in the questionnaire concerning dietary habits and physical activity. Based on the data provided by the students, the body mass index (BMI) was calculated before and during the pandemic. Results Young women (n = 388) living in rural areas dominated among the respondents. A significantly higher mean BMI value was observed in men compared to women (p <0.05). However, no significant changes in the value of BMI were observed before and during the pandemic, both in women and men. On the other hand, its higher average value was observed for men and women living in the city compared to those living in the countryside. The impact of the pandemic on the reduction of physical activity was observed by all respondents, especially those living in the city. Women noted a greater impact of the pandemic on eating behavior, compared to men. Conclusions The COVID-19 pandemic changed the dietary habits and physical activity of students at the State University of Applied Sciences in Nowy Sacz.